2019
DOI: 10.1108/gkmc-11-2018-0095
|View full text |Cite
|
Sign up to set email alerts
|

Roles of cataloguing librarians in the digital era

Abstract: Purpose This study aims to explore the roles and skills of Omani academic cataloguing librarians in facilitating access to various kinds of traditional and digital information resources and challenges confronting them in fulfilling that task. Design/methodology/approach Data for this research were gathered from 37 academic libraries in the country through a questionnaire sent to their cataloguing librarians. Google Docs format was used for cumulating and presenting quantitative data, whilst content analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Al Hijji and Al-Busaidi (2019) observed that, during the past two decades, the world has witnessed a huge revolution in information technology and communications reflected in publishing and accessing information resources. Library cataloguing also experienced large volumes of catalogue records on bibliographic utilities such as OCLC.…”
Section: Incorporating New Technologiesmentioning
confidence: 99%
“…Al Hijji and Al-Busaidi (2019) observed that, during the past two decades, the world has witnessed a huge revolution in information technology and communications reflected in publishing and accessing information resources. Library cataloguing also experienced large volumes of catalogue records on bibliographic utilities such as OCLC.…”
Section: Incorporating New Technologiesmentioning
confidence: 99%